Resistance Mechanisms to Anti-angiogenic Therapies in Cancer - Haibe, Yolla; Kreidieh, Malek; El Hajj, Hiba; Khalifeh, Ibrahim; Mukherji, Deborah; Temraz, Sally; Shamseddine, Ali (Frontiers in Oncology, 2020)
Tumor growth and metastasis rely on tumor vascular network for the adequate supply of oxygen and nutrients. Tumor angiogenesis relies on a highly complex program of growth factor signaling, endothelial cell (EC) proliferation, extracellular matrix (ECM) remodeling, and stromal cell interactions. Numerous pro-angiogenic drivers have been identified, the most important of which is the vascular endothelial growth factor (VEGF). The importance of pro-angiogenic inducers in tumor growth, invasion and extravasation make them an excellent therapeutic target in several types of cancers. Hence, the number of anti-angiogenic agents developed for cancer treatment has risen over the past decade, with at least eighty drugs being investigated in preclinical studies and phase I-III clinical trials. To date, the most common approaches to the inhibition of the VEGF axis include the blockade of VEGF receptors (VEGFRs) or ligands by neutralizing antibodies, as well as the inhibition of receptor tyrosine kinase (RTK) enzymes. Despite promising preclinical results, anti-angiogenic monotherapies led only to mild clinical benefits. The minimal benefits could be secondary to primary or acquired resistance, through the activation of alternative mechanisms that sustain tumor vascularization and growth. Mechanisms of resistance are categorized into VEGF-dependent alterations, non-VEGF pathways and stromal cell interactions. Thus, complementary approaches such as the combination of these inhibitors with agents targeting alternative mechanisms of blood vessel formation are urgently needed. This review provides an updated overview on the pathophysiology of angiogenesis during tumor growth. It also sheds light on the different pro-angiogenic and anti-angiogenic agents that have been developed to date. Finally, it highlights the preclinical evidence for mechanisms of angiogenic resistance and suggests novel therapeutic approaches that might be exploited with the ultimate aim of overcoming resistance and improving clinical outcomes for patients with cancer.